2003
DOI: 10.1161/01.hyp.0000088363.65943.6c
|View full text |Cite
|
Sign up to set email alerts
|

ET A Receptor Blockade Decreases Vascular Superoxide Generation in DOCA-Salt Hypertension

Abstract: Abstract-Development and progression of end-organ damage in hypertension have been associated with increased oxidative stress. Superoxide anion accumulation has been reported in deoxycorticosterone acetate (DOCA)-salt hypertension, in which endothelin-1 plays an important role in cardiovascular damage. We hypothesized that blockade of ET A receptors in DOCA-salt rats would decrease oxidative stress. Key Words: endothelin Ⅲ receptors, endothelin Ⅲ deoxycorticosterone Ⅲ hypertension, arterial Ⅲ oxidative stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 65 publications
9
97
1
4
Order By: Relevance
“…Callera et al 26 showed that in a deoxycorticosterone acetate-salt hypertension rat model, vascular superoxide production was increased by activation of the endothelin system. Zalba et al 27 demonstrated increased production of superoxide anion in SHRs.…”
Section: Interaction Of Oxidative Stress and Inflammation In The Devementioning
confidence: 99%
“…Callera et al 26 showed that in a deoxycorticosterone acetate-salt hypertension rat model, vascular superoxide production was increased by activation of the endothelin system. Zalba et al 27 demonstrated increased production of superoxide anion in SHRs.…”
Section: Interaction Of Oxidative Stress and Inflammation In The Devementioning
confidence: 99%
“…Also, in vivo blockade of ET A receptors in DOCA-salt hypertensive rats results in reduction in oxidative stress, supporting a role for ET-1 in the generation of reactive oxygen species. Since oxidative stress influences specific signaling pathways and redox-sensitive genes that coordinate several responses in the cardiovascular system including VSM growth and endothelial cell function, and because each of these alterations could be produced by ET-1, oxidative stress may play a role in the cardiovascular changes observed in DOCA-salt hypertension as a result of ET-1 overexpression/actions [83].…”
Section: Et and Oxidative Stressmentioning
confidence: 99%
“…51 Similarly, chronic ET-1 infusion is associated with Despite mixed results using the antioxidant tempol, there is clear evidence that ET stimulates superoxide production through an NADPH oxidase-dependent manner in DOCA-salt hypertensive rats. 55,56 Because ET A receptor blockade and superoxide scavenging can attenuate the hypertension associated with DOCA-salt treatment, it is reasonable to hypothesize that ETdependent hypertension could be inhibited by disruption of NADPH oxidase subunit assembly with the inhibitor, apocynin. Elmarakby et al have recently demonstrated that apocynin inhibits the increase in oxidative stress associated with chronic ET-1 infusion, yet the resulting hypertension was unaffected.…”
Section: Et B Receptors In Hypertensionmentioning
confidence: 99%
“…55,56 Because ET A receptor blockade and superoxide scavenging can attenuate the hypertension associated with DOCA-salt treatment, it is reasonable to hypothesize that ETdependent hypertension could be inhibited by disruption of NADPH oxidase subunit assembly with the inhibitor, apocynin. Elmarakby et al have recently demonstrated that apocynin inhibits the increase in oxidative stress associated with chronic ET-1 infusion, yet the resulting hypertension was unaffected.…”
Section: Et B Receptors In Hypertensionmentioning
confidence: 99%